GIS-based assessment of groundwater vulnerability to heavy metal contamination via water quality pollution indices in urban Aligarh, India - Mohd Saalim Badar; Shahrukh Ali; Daniyal; Md Wasim Akram; Kashif Faheem; Saif Ullah Khan; Izharul Haq Farooqi (Water Practice and Technology, 2024)
The study presents an assessment of groundwater vulnerability due to heavy-metal contamination using Heavy Metal Pollution and Contamination Index of Urban Aligarh. Globally, hazardous compounds in industrially contaminated sites are pressing and high-priority issue. A detailed risk assessment was carried out to determine the potential health hazards linked to locations that were recently polluted. A total of 17 groundwater samples were taken from hand-pump and 20 industrial drainage samples were collected from selected areas of Aligarh. The concentration of heavy-metals in the collected samples analyzed were shown on maps using ArcGIS software and interpreted for Heavy Metal Pollution Index (HPIx) and Contamination Index (CDx). These analyzed values were subsequently compared with the permissible limits established by the agencies like EPA, WHO, and BIS. The mean concentration of heavy-metals in groundwater of different locations was observed as follows particular sequence: Ni (1.40), Cu (0.58), Zn (0.06), Fe (0.08), Mn (0.04), Cr (0.001), Pb (0.00025) mg/l. Additionally in industrial effluent, Cr (18.3), Ni (13.34), Mn (1.16), Cu (1.99), Pb (1.2), Fe (6.3), Zn (0.51) mg/l. According to HPIx, the analysis reveals 64.7%, of visited areas belonged to have safe groundwater. Conversely, a smaller proportion, 35.3%, was found falling into heavy metal-polluted group. HIGHLIGHTS The study provides a comprehensive assessment of heavy metal contamination.; GIS-driven vulnerability mapping is conducted in the study.; The study includes an evaluation of real-world impact.; The study systematically validates scientific indices for accuracy and reliability.; The study investigates health effects resulting from heavy metal contamination.; A comprehensive analysis of drinking water quality.;